Non-Aufbau orbital ordering and spin density modulation in high-spin donor–acceptor conjugated polymers. Issue 38 (23rd September 2022) - Sabuj, Md Abdus; Muoh, Obinna; Huda, Md Masrul; Rai, Neeraj
Abstract : Spin topology and spin-orbital ordering can be controlled using atomistic engineering. Abstract : High-spin ground-state organic materials with unique spin topology can significantly impact molecular magnetism, spintronics, and quantum computing devices. However, strategies to control the spin topology and alignment of the unpaired spins in different molecular orbitals are not well understood. Here, we report modulating spin distribution along the molecular backbone in high-spin ground-state donor–acceptor (D–A) conjugated polymers. Density functional theory calculations indicate that substitution of different heteroatoms (such as C, Si, N, and Se) alters the aromatic character in the thiadiazole unit of the benzobisthiadiazole (BBT) acceptor and modulates the oligomer length to result in high-spin triplet ground-state, orbital and spin topology. The C, Si, and Se atom substituted polymers show a localized spin density at the two opposite ends of the polymers. However, a delocalized spin distribution is observed in the N substituted polymer. We find that the hybridization (sp 3 vs. sp 2 ) of the substituent atom plays an important role in controlling the electronic structure of these materials. This study shows that atomistic engineering is an efficient technique to tune the spin topologies and electronic configurations in the high-spin ground-state donor–acceptor conjugated polymers, compelling synthetic targets for room-temperature magnetic materials.